(untitled) (ENTHYMEMA, 2019)
The article proposes an analysis of W. G. Sebald’s Rings of Saturn as a text focused on an initiatory journey. In the text there seems to be a path of gradual transformations that progressively lead the traveller-narrator to a deeper form of knowledge of reality. The initiatory journey provides for the subject to get rid of the burden of Time, to enter post-existential dimension and finally to take a detached view of the world in order to regain a knowledge based on Analogy. Analogy, one of the key themes in the book, is seen as the regulating form of the cosmos and as the principle that can withstand Destruction through correspondences between human, natural and animal components of life.